(a+1)(a+3)(2a-a²)/(a³+a²)(a-2)(a+3)=-1/a=4/3
已知a=-3/4,求(a+1)(a+3)(2a-a²)/(a³+a²)(a-2)(a+3)
5个回答
相关问题
-
已知a=2/√3+1 求3-2a²-4a/a²+2a-1
-
已知a2+a-1=0求a3+3a2+a-4
-
已知a=³√4+³√2+1,求3\a+3\a²+1\a³
-
已知a1,a2,a3,a4成等比数列,且a1=a2+36,a3=a4+4,求a1,a2,a3,a4.
-
已知a1a2a3a4成等比数列,且a1=a2+36,a3=a4+4,求a1a2a3a4
-
已知a1,a2,a3,a4成等比数列,且a1=a2+36,a3=a4+4,求a1,a2,a3,a4.
-
已知a1,a2,a3,a4成等比数列,且a1=a2+36,a3=a4+4,求a1,a2,a3,a4.
-
已知A=4a²-3a,B=2a²+a-1,求2A-3B.
-
已知a^1/2+a^-1/2=4,求 (1)a+a^-1 (2)a^3/2-a^-3/2
-
(1) 已知a1,a2,a3,a4为等比数列,且a1=a2+36,a3=a4+4,求a1,a2,a3,a4.